A quantitative study of transepidermal water loss (TEWL) on conventional and microclimate management capable mattresses and hospital beds. Issue 4 (November 2019) - Denzinger, Markus; Rothenberger, Jens; Held, Manuel; Joss, Leonard; Ehnert, Sabrina; Kolbenschlag, Jonas; Daigeler, Adrien; Krauss, Sabrina
Abstract: Background: Transepidermal water loss (TEWL) is regarded as one of the most important parameters characterizing skin barrier integrity and has found to be higher in impaired skin barrier function. Reduced or low TEWL instead indicates skin barrier integrity or improvement. We evaluated if different mattresses/hospital beds can influence this skin barrier function by measuring TEWL before and after subjects lying in conventional and microclimate management capable mattresses/hospital beds. Methods: We included 25 healthy subjects in our study. Measurements were made using Courage & Khazaka Multi Probe Adapter MPA with Tewameter TM300 to determine TEWL before and after the subjects were lying in conventional (Viskolastic® Plus, Wulff Med Tec GmbH, Fedderingen, Germany and Duo™ 2 mattress, Hill-Rom GmbH Essen, Germany) or microclimate management capable mattresses/hospital beds (ClinActiv + MCM™ and PEARLS AFT, Hill-Rom GmbH Essen, Germany). Results: While there was no statistically significant difference in standard mattresses/hospital beds (22.19 ± 12.99 and 19.80 ± 11.48 g/hm 2 ), the decrease of TEWL was statistically significant in both microclimate management capable mattresses/hospital beds we investigated (16.89 ± 8.586 g/hm 2 and 17.41 ± 7.203 g/hm 2 ) compared to baseline values (35.85 ± 24.51 g/hm 2 ). Conclusion: As higher TEWL announces impaired skin barrier function these findings indicate that the choice of the mattress/hospital bed is important for skin barrier function and microclimate management systems improve skin barrier function of the skin.